The Impact of Investment Motivation, Risk Perception, and Literacy on Students' Interest in Investing in the Capital Market - Rafli Rafli; Kania Auliza; Yoga Yoga; Nabila Ramdani (PT Alahyan Publisher Sukabumi, 2025)
The number of students who are victims of online gambling makes the investment world have to provide education and be directed to real investment. The purpose of this study is to analyze and explain the impact of investment motivation, risk perception, literacy on students' interest in investing in the capital market. The method used in this study is quantitative descriptive.i.utu in the form of an overview with data obtained from the distribution of questionnaires to respondents.the population of this study is 4,000 students while the sample is taken using web.raoshop.com sample size calculator, with a distribution rate of 50%, an error rate of 10%, and a confidence level of 90%, so that a sample of 100 people is obtained. The results of this study explain that the influence of Motivation, Investment, Risk Perception, Literacy on Student Interest in Investing in the Capital Market has a positive and significant impact, with an influence of 0.628 or 62.8% while the remaining 38.2% is influenced by other variables outside this study.